Fluorescent UV-curable Polyurethane Acrylate Nanocomposite Coatings Strengthened with Carbon Quantum Dots: Preparation and Investigation of UV-blocking and Anti-Corrosive Properties - Abbas Madhi; Behzad Shirkavand Hadavand; Mohammad Hassan Madhi; Zahra Rahmani (شیمی کاربردی روز)
Most polymers exposed to UV radiating from the sun deteriorate and lose their mechanical features. Polymer coatings are generally used for protection of metal surfaces against corrosive factors. Thus, production of coatings blocking the sunlight UV rays is necessary to protect the metal surfaces. This work mainly focuses on synthesis of fluorescent bio-based UV-curable polyurethane acrylate (PUA) and studies the changes occurred in the various specifications of these coatings resulted from adding carbon quantum dots (CQDs). To synthesize PUA oligomer, castor oil was applied as a natural and biocompatible substance instead of chemical polyols. By pyrolysis of the starch and water blend, CQDs were synthesized using microwave-assisted method. To characterize the synthesized coatings and to analyze the reinforcing effect of CQDs on the resultant nanocomposite, electroscopic methods were utilized. Adding CQDs 0.5 wt% to PUA resin resulted in improvement of adhesion strength and thermal stability in PUA/CQDs (0.5 wt%) coating compared to PUA (pure) coating. With exposing PUA/CQDs to UV rays, blue fluorescence was emitted and strong absorption bands also appeared in all of the UV regions. Most of the UV rays passed through the PUA film, while PUA/CQDs blocked higher than 99% of UV radiation. Results from salt spray and EIS tests confirmed that resistance to corrosion was improved in PUA/CQDs coating versus the pure coating.